NASIONALISME PEREMPUAN D(AR)I JAWA KAJIAN BUDAYA ATAS NOVEL DURGA UMAYI Y.B. MANGUNWIJAYA - A. Windarto (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
The 1945-1949 Indonesian Revolution was a historic time and place, especially for those who witnessed and experienced such a terrible event. Through his novel entitled Durga Umayi (1991), Y.B. Mangunwijaya or Father Mangun, were able to narrate the steps of the nationalist women. Although committed